MHD natural convection and entropy analysis of a nanofluid inside T-shaped baffled enclosure. Issue 12 (24th October 2018) - Armaghani, Taher; Kasaeipoor, A.; Izadi, Mohsen; Pop, Ioan
Abstract : Purpose: The purpose of this paper is to numerically study MHD natural convection and entropy generation of Al2 O3 -water alumina nanofluid inside of T-shaped baffled cavity which is subjected to a magnetic field. Design/methodology/approach: Effect of various geometrical, fluid and flow factors such as aspect ratio of enclosure and baffle length, Rayleigh and Hartmann number of nanofluid have been considered in detail. The hydrodynamics and thermal indexes of nanofluid have been described using streamlines, isotherms and isentropic lines. Findings: It is found that by enhancing Hartmann number, symmetrical streamlines gradually lose symmetry and their values decline. It is found that by enhancing Hartmann number, symmetrical streamlines gradually lose symmetry and their values decline. The interesting finding is an increase in the impact of Hartmann number on heat transfer indexes with augmenting Rayleigh number. However, with augmenting Rayleigh number and, thus, strengthening the buoyant forces, the efficacy of Hartmann number one, an index indicating the simultaneous impact of natural heat transfer to entropy generation increases. It is clearly seen that the efficacy of nanofluid on increased Nusselt number enhances with increasing aspect ratio of the enclosure. Based on the results, the Nusselt number generally enhances with the larger baffle length in the enclosure. Finally, with larger Hartmann number and lesser Nusselt one, entropy production is reduced. Originality/value: The authors believe that all the results, both numerical and asymptotic, are original and have not been published elsewhere.